KEBIJAKAN PENDIDIKAN JASMANI DALAM PENDIDIKAN - Lengkana, Anggi Setia; Sofa, N. Siti Nuraeni (STKIP Pasundan, 2017)
Education in Indonesia is now increasingly growing, although there are some people who say that education in Indonesia has fallen. In essence, it is not the outcome of the worst education but the standard of education which always increases every year. When compared with developed countries, education in Indonesia is still relatively low, but when compared with other developing countries, the quality of education in Indonesia deserves to be categorized as good. The policies that regulate education are already very numerous, making it easier and providing space for Indonesian education personnel to continue to innovate and build character education in accordance with national education expectations.